(Spices Irradiation Treatment for Presevation and Hygiene Purpose) - Sudibyo, Agus (Warta Industri Hasil Pertanian, 1994)
Spices are important commodity in international trade and ussually added to food in only small amounts. They have little or no nutritional value; their importance lies not only in their ability to impart their own characteristic flavour to food but also to enhance the natural flavour of food it self. However, spices are ussually contaminated with numerous microorganisms and this causes serious problem for the food industry.Various alternatives to the uses of ground spices (such as the use spice oleoresins and essential oils) exist, althought these have certain limitation in their application. Gas fumigation of spices is also simple but a greater disadvantage of this methods is the danger of chemical residues in the food.An effective method of sterilization by irradiation would,threfore,hold,considerable interest for the food industry.This paper rieviewedÂ  contamination of spices,spices irradiation treatment and the effect of irradiation upon organoleptic properties and chemical constituents of spices.